Eco‐friendly magnetic nanoscavengers as emerging materials for improving reclaimed water quality - Santiago, Estephany (My University, 2021)
Magnetic nanoparticles are synthesized and modified during a chemical co‐precipitation to produce three different magnetic nanoscavengers: nanomagnetite‐chitosan, nanomagnetite‐nanodiamond and nanomagnetite‐chitosan grafted with a carbamoyl benzoic acid. These magnetic nanoscavengers are characterized by Fourier transform infrared spectroscopy, thermogravimetric analysis, dynamic light scattering, zeta potential, and scanning transmission electron microscopy, to prove their correct synthesis. The magnetic nanoscavengers are tested as nano‐adsorbents to improve reclaimed water (RW) quality. Special attention is given to changes in RW properties, explaining them as the interfacial interaction between ionic species and nanoscavengers surface. At the same time, the ability of nanoscavengers to remove alkalinity and hardness in RW is demonstrated at pH 7, 8, and 9.
Advanced sustainable systems
Keywords: Nanoscavengers; Emerging materials; Campus Tijuana